Bridging employees’ perceptions of corporate social responsibility, sense-making for meaningfulness, and work engagement for successful self-regulation - Wang, Z.; Carroll, S.; Wang, E.H. (Behavioral Sciences, 2024)
In response to calls for research on the psychological mechanisms, such as perceptions and attitudes toward corporate citizenship, in promoting positive outcomes at work, this research presents a novel approach by empirically testing a calling conditioned path model from P perception of corporate CSR (P-CSR) to work engagement via meaningfulness under the theoretical framework of self-determination theory. Survey data collected from 224 corporate employees in the US were tested using the PROCESS plugin (version 4.3) in SPSS. The regression results supported the positive direct and indirect paths from employees’ P-CSR to meaningfulness and work engagement but not the conditioning effect of calling work orientation. This study’s unique findings, limitations, future research, and implications are discussed, expanding micro-CSR research and unboxing the management assumptions of employees as purposeful autonomous agents seeking consistent interpretations and authentic perceptions of organizational CSR activities during their sense-making processes. Non-confirming of the calling conditioning the path model shed light on it being a dynamic multi-dimensional and multi-level construct to be further researched. © 2024 by the authors.
Keywords: calling work orientation; dept.mgt; micro-CSR; peer-reviewed; work engagement

A metacognitive approach to understanding what marker variables measure - Leonard, Stephanie; Simmering, Marcia J.; Wall, Alison E. (Current Psychology, 2024)
Marker variables provide an efficacious means of post hoc detection of common method variance (CMV) in data. These variables are measured in the same way as substantive variables, but because they are conceptually unrelated to the variables of interest, they are believed to be a proxy for CMV. Although marker variables have demonstrated effectiveness, questions remain as to what they actually measure, and thus, why they work. This lack of knowledge prevents researchers from choosing appropriate marker variables to include in same source surveys. The purpose of this research is to determine how four different marker variables account for common rater effects which can cause CMV. A metacognitive approach is used to develop an empirical study using two samples, with a focus on the specific rater effects of mood state, transient mood, consistency motif, and illusory correlations. Findings indicate that these marker variables elicit similar respondent reactions and do not create a notable psychological separation between substantive variables. Additionally, there is evidence that respondents’ use of consistency motifs and illusory correlations influence substantive variable relations. Finally, using the confirmatory factor analysis marker technique, data from two samples indicate the presence of CMV, but not bias from CMV, indicating that the problem of artificially inflated results due to CMV may be overstated.
Keywords: Common method variance; Marker variables; Metacognition; Survey research; dept.mgt; peer-reviewed

The interplay of power, incentives, academic freedom, and gender equity - Wieland, Alice; Jansen, Amy (Journal of Academic Freedom, 2024)
Alice Wieland and Amy Jansen explore the intersection of how power, adverse incentives, and gender bias combine to perpetuate gender inequity in higher education.
Keywords: dept.lib; dept.mgt

Do schools have hindrance of quality to promote innovativeness? Examining the role of empowering leadership and stakeholder involvement - Birasnav, M.; Dahiya, Rinki; Bharti, Teena (International Journal of Quality & Reliability Management, 2024)
Purpose Schools provide high priorities to offer innovative curricular and cocurricular programs, and leaders make necessary efforts to promote enablers and overcome disablers for sustaining their innovativeness. With the background of quality management and stakeholder theories, the present study examines the interplay of hindrances to quality between empowering leadership, stakeholder involvement and organizational innovativeness. Design/methodology/approach Responses of 157 American school principals collected through the Teaching and Learning International Survey 2018 by the Organization for Economic Cooperation and Development were used and analyzed to test the proposed hypotheses. Findings Results show that empowering leadership behaviors of school principals support promoting organizational innovativeness, and involvement of stakeholders with the school activities also promotes organizational innovativeness. Interestingly, when American schools faced a high level of hindrance to providing quality education to their students, principals’ high level of empowering leadership behaviors promoted organizational innovativeness. Originality/value This is the first time in the literature that the interplay between empowering leadership, stakeholder involvement and hindrance of quality education has been examined to promote organizational innovativeness.
Keywords: Empowering leadership; Hindrance of quality education; Organizational innovativeness; Quality management; Stakeholder involvement; dept.mgt; peer-reviewed

Unboxing the temporal patterns of employee engagement: a daily and weekly analysis of needs satisfaction, work motivation and employee well-being - Wang, Z. (Evidence-based HRM, 2024)
Purpose: This research used a temporal approach to operationalize employee engagement, capturing subjective/objective time of the day and day of the week to analyze the dynamic patterns of employees’ daily/weekly well-being, basic needs satisfaction, and situational work motivation under the integrated framework of self-determination theory. Design/methodology/approach: Multi-level data was collected using the survey structure outlined under the day reconstruction methodology (DRM) with samples of Canadian part-time working undergraduate students and full-time US corporate employees (1980 work episodes reported by 321 participants). Findings: Multi-level confirmatory factorial analysis results supported the measurement invariance for within-person variables in all the working episodes across the US and Canada samples. Structural equation modeling path analysis results, using the within-person variables, captured the daily temporal patterns that employees’ well-being (vitality and positive affect), basic psychological needs (autonomy and relatedness), and situational autonomous motivation started at a high level and decreased with both subjective and objective time of the day. Negative affect showed asymmetric daily and weekly temporal patterns compared to positive affect. A few indirect paths were found, including one from the subjective time of the day to employee well-being (vitality and affect) via situational autonomous motivation and another one from the day of the week to vitality and positive affect via relatedness needs satisfaction and situational autonomous motivation. Research limitations/implications: The socio-cultural and business impacts of work scheduling practices and implications for theory-driven, evidence-based organizational development practices were discussed together with the research limitations. Practical implications: Results on how the variations in self-regulation during the performance of different work tasks in a single work event help practitioners to connect repeated situational motivational change patterns to effective supervision. HR business partner can also utilize such findings to shape evidence-based practice to improve employee engagement. Originality/value: This research is one of the few pioneer studies to look into how temporal factors, such as work scheduling, affect employees' well-being through the dynamic understanding of the mediated path model from time to employee well-being via psychological engagement conditions such as motivation and needs satisfaction. © 2024, Emerald Publishing Limited.
Keywords: Self-regulation; Temporal analysis; Work scheduling; dept.mgt; peer-reviewed